Criticizing Montessori’s Method of Early Childhood Education using Islamic Psychology Perspective - Septi Gumiandari; Ilman Nafi'a; Dindin Jamaluddin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2019)
This study examined critically Montessori’s concepts on early childhood education through Islamic Psychology perspective. This research used qualitative methodology with a literature approach. The results showed that (1) Montessori’s method pays more attention to the cognitive aspect of children development while children potential doesn’t only consist of cognitive, affective, and psycho-motoric aspects, but also spiritual one; (2) Reinforcement are not needed in Montessori’s method, while in Islamic Psychology, rewards can increase children's learning and punishment is needed to make children become disciplined in carrying out the rules; (3) Learning environment should be structured, in order, realistic and natural. This concept is suitable for upper class educational institutions but it would be difficult for middle-low income groups since the materials required by Montessori’s method is expensive enough. (4) Parents and teachers are required to become observers and interpreters. This role may pose problem on the part of parents and teachers since not all parents and teachers have criteria to act as is it expected by Montessori’s method.